Social image concerns and pro-social behavior - Nicola Lacetera; Mario Macis (Institute for the Study of Labor (IZA), 2008)
Using longitudinal data on the entire population of blood donors in an Italian town, we examine how donors respond to an award scheme which rewards them with medals when they reach certain donation quotas. Our results indicate that donors significantly increase the frequency of their donations immediately before reaching the thresholds for which the rewards are given, but only if the prizes are publicly announced in the local newspaper and awarded in a public ceremony. The results are robust to several specifications, sample definitions, and controls for observable and unobservable heterogeneity. Our findings are consistent with social image concerns being a primary motivator of pro-social behavior, and indicate that symbolic prizes are most effective as motivators when they are awarded publicly. Because we do not detect a reduction in donation frequency after the quotas are reached, this incentive based on social prestige leads to a net increase in the frequency of donations.
urn:nbn:de:101:1-20081126268
Keywords: D12; 330; Incentives; awards; public good provision; pro-social behavior; public health; social prestige; Blutspende; Ökonomischer Anreiz; Prestige; Altruismus; Soziales Verhalten; Italien